Levetiracetam alleviates cognitive decline in Alzheimer’s disease animal model by ameliorating the dysfunction of the neuronal network - Zheng, Xiang-Yu; Zhang, Hai-Chen; Lv, Yu-Dan; Jin, Feng-Yan; Wu, Xiu-Juan; Zhu, Jie; Ruan, Yang (Frontiers in Aging Neuroscience, 2022)
Background Patients with Alzheimer’s disease (AD) have a significantly higher risk of seizures than other individuals in an age-matched population, suggesting a close association between epilepsy and AD. We aimed to examine the effects of levetiracetam (LEV)—a drug for treating seizures—on learning and memory and the neuropathological features of AD. Methods We crossbred APP23 mice with microtubule-associated protein tau (MAPT) transgenic mice to generate APP23/MAPT mice. These mice were treated with different concentrations of LEV in the presence of kainic acid (KA) for 3 months. Results Low doses of LEV alleviated the effects of KA on memory defects in APP23/MAPT mice. Mechanistic investigations showed that low concentrations of LEV decreased tau phosphorylation by reducing the activities of cyclin-dependent kinase 5 and glycogen synthase kinase 3α/β, thus rescuing neurons from synaptic dystrophy and apoptosis. Low doses of LEV inhibited the effects of KA (i.e., inducing neuroinflammation and impairing the autophagy of amyloid β-peptide), thus improving cognitive decline. High concentrations of LEV decreased the production and deposition of amyloid β-peptide (Aβ) by reducing the expression of β-site APP-cleaving enzyme 1 and presenilin 1. However, high concentrations of LEV also induced neuronal apoptosis, decreased movement ability in mice, and did not alleviate cognitive decline in AD mice. Conclusion Our results support the hypothesis that aberrant network activity contributes to the synaptic and cognitive deficits in APP23/MAPT mice. A low concentration of LEV may help ameliorate abnormalities of AD; however, a high LEV concentration did not induce similar results.